Особенности фазо-частотных характеристик рекурсивных компонент первого порядка - Сильчук, А. В.; Ситников, В. С. (Видавництво Львівської політехніки, 2011)
Features of recursive first-order component’s phase response. The analysis of the phase response of polynomial and non-polynomial filters for further approximation to the linear control this characteristic.
Keywords: фильтр; передаточная функция; фазо-частотная характеристика